Effective work practices for FLOSS development: A model and propositions - Kevin Crowston; Annabi, Hala; James Howison; Masango, Chengetai (Proceedings of the 38th Hawai'i International Conference on System Sciences (HICSS), 2005)
We review the literature on Free/Libre Open Source Software (FLOSS) development and on software development, distributed work and teams more generally to develop a theoretical model to explain the performance of FLOSS teams. The proposed model is based on Hackman’s [1] model of effectiveness of work teams, with coordination theory [2] and collective mind [3] to extend Hackman’s model by elaborating team practices relevant to effectiveness in software development. We propose a set of propositions to guide further research.
"Effective work practices for Software Engineering: Free/Libre Open Source Software Development". Presentation at the Workshop on Interdisciplinary Software Engineering 2004, SIGSOFT 2004/FSE-12 Conference, Newport Beach, CA, 5 November. Powerpoint file.